70 Anaesthetic management of patients undergoing aortopexy: a 4 year review. (30th November 2020) - Lau, Norlan; George, Marina; Butler, Colin; Muthialu, Nagarajan; Coppi, Paulo de
Abstract : Objectives: Aortopexies are part of GOSH's specialist tracheal services offered to children with severe tracheobronchomalacia, with an average of 10 cases performed per year. We wanted to identify safe and effective aspects of the anaesthetic care within this complex group of patients undergoing the procedure. Methods: We looked at patient characteristics and anaesthetic management of 26 aortopexies over 4 years with a view to creating some guidance for future practice. Findings: 26 patients (weight range 2.6 – 40 kg, from corrected gestational age of 38 weeks to 15 years of age) underwent aortopexies via the median sternotomy (n=15), thoracotomy (n=2) and thoracoscopic (n=9) approaches. These patients had complex medical backgrounds, including vascular compression of the trachea and trachea-oesophageal fistulae. The anaesthetic approach was tailored to the surgical approach, with median sternotomy (MS) and thoracotomies (To) requiring more analgesia, blood transfusions, invasive monitoring and use of longer-acting muscle relaxants to facilitate safe transfer to Intensive Care (ICU), compared to the thoracoscopic (Tc) approaches. All but one of the patients required postoperative ICU care. The median time to extubation was 2 days and the median stay in ICU was 5 days. The intraoperative course seemed safe overall with no documented intraoperative cardiac arrests and/or deaths. The MS and To cases were carried out in cardiothoracic theatres whereas the Tc cases were performed in general theatres. All the patients were fully paralysed and intubated for the procedure, with no noted trend of difficult intubations. 3 cases required blood transfusions of 10–20 ml/kg and no further blood component. Conclusions: We have been able to highlight areas contributing to safe care of this heterogeneous group of patients, including availability of ICU beds and appropriate location of surgery. Doing a prospective study in future will address some of the limitations of comparing these groups retrospectively.